2021
DOI: 10.3390/cells10123276
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Pullulan-Collagen-Gold Nano Composite Improves Mesenchymal Stem Cells Neural Differentiation and Inflammatory Regulation

Abstract: Tissue repair engineering supported by nanoparticles and stem cells has been demonstrated as being an efficient strategy for promoting the healing potential during the regeneration of damaged tissues. In the current study, we prepared various nanomaterials including pure Pul, pure Col, Pul–Col, Pul–Au, Pul–Col–Au, and Col–Au to investigate their physicochemical properties, biocompatibility, biological functions, differentiation capacities, and anti-inflammatory abilities through in vitro and in vivo assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…As shown in Figure A–C, the ECM-mineralized nodule formation of cells treated with miR-29b conjugated to PEI-capped AuNPs provides the highest calcium deposition after staining with Alizarin red S. From this work, it is clearly demonstrated that the modification of AuNPs and then functionalization with molecules involved in the osteogenic differentiation of hMSCs and MC3T3-E1 cells could effectively develop the cell differentiation process for use in tissue engineering and regenerative medicine. The recent surface modification of AuNPs using natural materials (pullulan and collagen) to enhance the neuron differentiation in human MSCs and endothelialization induction was demonstrated by Yang et al This can be a good example of increasing the biological performance of AuNPs in modulating cell differentiation in combination with biological materials.…”
Section: Roles Of Aunps In Cell Differentiationmentioning
confidence: 99%
“…As shown in Figure A–C, the ECM-mineralized nodule formation of cells treated with miR-29b conjugated to PEI-capped AuNPs provides the highest calcium deposition after staining with Alizarin red S. From this work, it is clearly demonstrated that the modification of AuNPs and then functionalization with molecules involved in the osteogenic differentiation of hMSCs and MC3T3-E1 cells could effectively develop the cell differentiation process for use in tissue engineering and regenerative medicine. The recent surface modification of AuNPs using natural materials (pullulan and collagen) to enhance the neuron differentiation in human MSCs and endothelialization induction was demonstrated by Yang et al This can be a good example of increasing the biological performance of AuNPs in modulating cell differentiation in combination with biological materials.…”
Section: Roles Of Aunps In Cell Differentiationmentioning
confidence: 99%
“…For example, Yang et al investigated the immunomodulatory effect of culturing WJMSCs with various groups, namely Pullulan (Pul)‐Col, Pul‐Col‐AuNPs, Pul‐AuNPs, Pul, and Col, in a Sprague–Dawley rat model; the AuNPs solution was coated on a 15 mm glass coverslip and implanted in the subcutaneous tissue (Figure 4a ). 95 After 4 weeks, CD45 expression (indicative of leukocyte infiltration induced by M1 macrophages) was lowest at ~0.56‐fold in the Pul‐Col‐AuNPs group, followed by ~0.64‐fold in Col‐AuNPs, and ~0.7‐fold in Pul‐AuNPs. CD163 staining showed a ~1.5‐fold increase in expression for the Pul‐Col‐AuNPs group, followed by a ~1.4‐fold increase for the Col‐AuNPs group, and a ~1.3‐fold increase for the Pul‐AuNPs group.…”
Section: Msc‐biomaterials Therapies For Treating Chronic Non...mentioning
confidence: 93%
“…( # p < 0.05, &&& p < 0.001, * p < 0.05, *** p < 0.001). Reprinted from Reference 95 , Copyright (2021), with permission from the authors. (b) (i) Schematic of a reduced graphene oxide (RGO)‐loaded acellular dermal matrix (ADM) loaded with MSCs tested on a diabetic mouse wound model.…”
Section: Msc‐biomaterials Therapies For Treating Chronic Non...mentioning
confidence: 99%
“…Because of its low rejection rate, high biocompatibility, 70 biodegradability, 71 workability, and lack of viral infection risk, Human-like collagen (HLC) has been used in hydrogels, 72 vascular scaffolds, 73 and artificial bones. 74 Several papers have reported on the development of hydrogels using chitosan or chitosan derivatives, hyaluronic acid, collagen, or other cross linking agents.…”
Section: Collagen Based Pullulanmentioning
confidence: 99%